(untitled) (Research, Society and Development, 2022)
Depression is an emotional state that can be experienced by anyone at some point in their life. Therefore, distinguishing the “normal” emotion of depression to an illness that requires medical treatment is problematic for people who are not trained in the mental health sciences. The increase in the use of antidepressant drugs, resulting from the COVID-19 epidemic, becomes a matter of public health concern. The present work deals with the increase in the number of people diagnosed with depression during the COVID-19 pandemic. As a result, the use of antidepressant drugs has increased. The information was obtained through the medical report/prescriptions. The survey was carried out in a certain period of 2019 and 2020, as a way to compare the pre and post pandemic. The purpose of the survey is to assess the increase in antidepressant use during the COVID-19 pandemic, according to data provided by the company. In view of the results of the analysis of the report/medical prescriptions in the Family Health Strategy, in the municipality of Lindoeste, a higher prevalence was observed in adult consumers (63.45%) of the female gender (76.89%). The most consumed antidepressants were those belonging to the Tricyclics (ADTs) class, corresponding to 45%. According to the analysis, the most prescribed drugs were Fluoxetine 20mg, which obtained 55% of prescriptions and Amitriptyline 25mg, which had 40.84%, being observed that most prescriptions were written by general practitioners (88.66% ).